2014
DOI: 10.1039/c4ra05390g
|View full text |Cite
|
Sign up to set email alerts
|

Role of zinc and copper metal ions in amyloid β-peptides Aβ1–40and Aβ1–42aggregation

Abstract: Conformational structural changes of Aβ1–40 and Aβ1–42 monomers during the interaction of Cu2+ and Zn2+ metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 58 publications
(97 reference statements)
7
47
0
Order By: Relevance
“…The Aβ 40 generates a monomer, dimer, trimer, and tetramer, whereas Aβ 42 forms pentamer, hexamer, dodecamers, octadecamers, and oligomers. Between these two pepides, Aβ 42 has exhibits greater aggregation propensity than Aβ 40 peptide . The Aβ 42 monomer is the basic building block to aggregation of dimer, trimer and oligomers, so the structural characterization of the monomer at atomic level is important to explain the aggregation mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aβ 40 generates a monomer, dimer, trimer, and tetramer, whereas Aβ 42 forms pentamer, hexamer, dodecamers, octadecamers, and oligomers. Between these two pepides, Aβ 42 has exhibits greater aggregation propensity than Aβ 40 peptide . The Aβ 42 monomer is the basic building block to aggregation of dimer, trimer and oligomers, so the structural characterization of the monomer at atomic level is important to explain the aggregation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zn 2+ promotes rapid formation of non‐fibrillar aggregates, whereas Cu 2+ enhances the proportion of β‐sheet content in both Aβ 40 and Aβ 42 peptides. The increased proportion of β‐sheet for copper‐bound Aβ indicates the propensity of aggregation . The Fe 2+ is more concentrated in amyloid plaques .…”
Section: Introductionmentioning
confidence: 99%
“…The monomers are initially separated in the simulation cell, then aggregate to form stable dimers through salt-bridge and hydrophobic contacts. In our previous work, 31 it has been confirmed that the conformations of Ab 42 have interactions between the central hydrophobic core LVFFA (17)(18)(19)(20)(21) and hydrophobic c-terminus (Met35-Ala42) because of the distance of around 4-6.5 Å between the Ca(Val24)-Ca(Asn27) residues. In our previous work, 31 it has been confirmed that the conformations of Ab 42 have interactions between the central hydrophobic core LVFFA (17)(18)(19)(20)(21) and hydrophobic c-terminus (Met35-Ala42) because of the distance of around 4-6.5 Å between the Ca(Val24)-Ca(Asn27) residues.…”
Section: Deformation Energy Analysismentioning
confidence: 74%
“…The intermolecular saltbridge is formed between the residues Asp 23 and Lys 28 in the turn region of amino acids Ser26-Ile31. The average distance of the CO 2 À moiety of Asp 23 from the NH 3 À moiety of the Lys 28 residue in the intra-and inter-peptide salt-bridge 31 have been calculated and given in the Table 2 and Fig. 52 The salt-bridge formation between the Asp 23 and Lys 28 residues of the peptide is the driving force for joining the long networks of layered b sheets in the Ab peptides.…”
Section: Variation Of Salt-bridge (Asp 23 /Lys 28 ) Distancesmentioning
confidence: 99%
See 1 more Smart Citation